Assessing High School Students' Misconceptions of the Human Reproductive System Using a Three-Tier Diagnostic Test - Rahmat Baharuddin; Ramadhani; Mohammad Farhan Umar (Pro-Life, 2026)
Misconceptions about reproductive system topics remain a persistent challenge in high school biology learning. This study aimed to assess students' misconceptions about the reproductive system using a three-tier diagnostic test. A descriptive quantitative method was employed involving 57 twelfth-grade students from a senior high school in Parepare, South Sulawesi. Data were collected using a three-tier diagnostic test covering six reproductive system subtopics and analyzed descriptively by classifying students' conceptions into scientific understanding (SU), misconception (Mi), and lack of knowledge (LoK). The results revealed misconceptions across all six subtopics of the reproductive system. The highest percentage of misconceptions was found in reproductive hormone regulation (38.60%), followed by gametogenesis (35.09%). Meanwhile, the highest percentage of lack of knowledge was observed in reproductive system disorders (45.61%) and gametogenesis (43.86%). In contrast, reproductive organs showed the highest percentage of scientific understanding (57.89%). Overall, the findings indicate that students still experience considerable misconceptions and conceptual difficulties in several reproductive system subtopics, particularly those involving abstract processes and hormonal mechanisms. These findings highlight the need for targeted instructional interventions, especially in subtopics with high rates of misconceptions and lack knowledge levels, to support conceptual change and improve students' scientific understanding.